Active Learning to Develop Motor Skills and Teamwork - Johanna Lorena Aristizabal-Almanza (Revista Electronic@ Educare, 2017)
This action-research project was conducted to determine how the use of principles of active learning, specifically collaboration, had an effect on psychomotor performance and achievement in teamwork. The research setting included 20 students of first grade from a private school located in Bogota, Colombia. The students were selected through not randomized sampling based on criteria. The methodological process included observation, interviews, and a scale based on standardized tests to measure skills; the latter was applied before and after the intervention. Data analysis was performed using a triangulation of qualitative data, and through comparative analysis of the initial and final student profile for quantitative inputs. The results showed that, after the intervention with collaborative techniques based on action learning, students achieved a positive variation in their performance. Being part of a team positively affected the achievement of the objectives. Systematical reflection on their practices fostered their capacity to identify strengths and weaknesses to build knowledge in interaction with others. Knowledge construction was nurtured based in their previous experiences. Students showed more accountability and self-directed learning behaviors, according to their age. Overall the experience showed the importance of research and innovation in the classroom in order to provide meaningful data, so teachers and researchers can engage in providing learning experiences based in active learning.